ANALYSIS OF THE EFFECT OF NOISE INTENSITY DB(A) IN THE PRODUCTION PROCESS ON HEARING LOSS IN A COMPRESSOR MANUFACTURING PLANT - Andara, Nurul Dwi; Akmal, Muhammad; Margana, Ade Suryatman; Yuningsih, Nani; Ayu, Wirenda Sekar; Muliawan, Rizki (JURNAL CRANKSHAFT, 2026)
Noise is one of the most common physical hazards in industrial environments and may adversely affect both health and workplace comfort. This study aims to analyze noise intensity during production processes and its impact on workers’ comfort perception at compressor manufacturing plant, as well as to estimate the potential risk of permanent hearing loss using the Noise-Induced Permanent Threshold Shift (NIPTS) method based on ISO 1999:2013. A descriptive quantitative approach was employed, consisting of noise measurements at five production points over three working days and the distribution of questionnaires to 31 respondents to assess perceptions regarding comfort, communication disturbance, concentration, and physical complaints. The results indicated that noise intensity in several areas, particularly frame manufacturing and sandblasting, exceeded the threshold limit of 85 dB(A), with the highest level reaching 117.6 dB(A). NIPTS calculations showed that workers in these areas were at high risk of permanent threshold shifts, with values ranging from 31.28 to 69.77. In contrast, the bending machine area presented noise levels closer to the threshold, with relatively low NIPTS values (0.30–0.71), suggesting a lower risk of long-term auditory impairment. Questionnaire results revealed that 50% of workers perceived noise levels as severe, 29.2% as moderate, and 20.8% as mild. The majority also reported that noise slightly interfered with their concentration and comfort, although most were able to adapt to the working conditions. In conclusion, noise exposure in the production environment of compressors manufacturing plant poses both auditory and non-auditory health risks. Therefore, comprehensive noise control strategies, including engineering modifications, administrative measures, and consistent use of personal protective equipment, are required to safeguard workers’ health and support sustainable productivity.